Hubungan Kemandirian Belajar dan Hasil Belajar Matematika Siswa Sekolah Dasar di Kecamatan Buluspesantren - Larasati, Icha; Joharman, Joharman; Salimi, Moh (Universitas Pendidikan Indonesia Kampus Serang, 2020)
This study aimed to prove the existence of a positive correlation between students’ self-regulated learning and mathematics learning outcomes of fourth grade students and to know the magnitude of the contribution of self-regulated learning to the mathematics learning outcomes of fourth grade students in Buluspesantren. This research was a quantitative research by correlational method. Sampling was done by cluster random sampling technique with the help of SPSS application version 18. The number of samples in this study was 266 students in eleven State Elementary Schools throughout the Buluspesantren district. The data retrieval used questionnaires and tests. Data analysis used Pearson product moment correlation test with a significance level of 0.05 and used effective contributions. In testing the correlation, it was obtained sig = 0.000 (sig 0.05), meaning that there was a positive and significant relationship between self-regulated learning and mathematics learning outcomes which showed the higher the self-regulated learning skill of students, the higher the mathematics learning outcomes of students. On the other hand, the lower the self-regulated learning skill of students, the lower the mathematics learning outcomes of students. Self-regulated learning skill contributed to mathematics learning outcomes by 20.35%. The results of this study were in accordance with existing theories and are also supported by relevant research